Assessment of Nurses' Knowledge and Practices Regarding Infection Control Measures in Tertiary Care Hospitals of Pakistan - Parveen, Nusrat; BiBi, Gulshad (Biological and Clinical Sciences Research Journal, 2025)
Infection control is a cornerstone of patient safety in healthcare settings. Nurses play a vital role in implementing infection prevention protocols, yet disparities often exist between their knowledge and actual practices. In Pakistan, healthcare-associated infections (HAIs) remain a significant concern due to suboptimal compliance with standard precautions. Objective: This study aimed to assess the knowledge and practices of registered nurses regarding infection control measures in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted at tertiary care hospitals from April to September 2024. A total of 58 registered nurses were selected through purposive sampling. Data were collected using a structured, pre-validated questionnaire comprising demographic details, knowledge-based questions, and practice-related items aligned with WHO and CDC infection control guidelines. Data were analysed using SPSS version 26, with descriptive statistics and Pearson's correlation to assess the relationship between knowledge and practice. A p-value <0.05 was considered statistically significant. Results: Among the 58 nurses, 31% demonstrated good knowledge, 44.8% had moderate knowledge, and 24.2% had poor knowledge of infection control. Practice assessment showed that 34.5% exhibited good practices, 46.6% moderate, and 18.9% poor practices. A statistically significant positive correlation (r = 0.64, p < 0.001) was found between knowledge and practice scores. Nurses with higher qualifications and more clinical experience performed better in both domains. Conclusion: The study highlights moderate infection control knowledge and practice levels among nurses, with apparent gaps requiring attention. Strengthening infection control training and regular competency evaluations are essential for improving adherence and reducing the burden of HAIs in Pakistani healthcare settings.